Chiral phosphoric acid-catalyzed asymmetric dearomatization reactions - Xia, Zi-Lei; Xu-Xu, Qing-Feng; Zheng, Chao; You, Shu-Li (Chemical Society reviews, 2020)
We summarize in this review the recent development of chiral phosphoric acid (CPA)-catalyzed asymmetric dearomatization reactions. A wide array of electron-rich arenes (indoles, phenols, naphthols, benzothiophenes, benzofurans, etc. ) and electron-poor arenes (pyridines, quinolines, isoquinolines, etc. ) has been proved reactive towards various reaction partners in the presence of a CPA catalyst, enabling asymmetric dearomatization reactions that lead to structurally-diverse polycyclic molecules. The reactions are grouped according to the roles of the arenes in the reactions (as nucleophiles or electrophiles) and the types of reaction partners. This review closes with a personal perspective on the dynamic research area of asymmetric dearomatization reactions by CPAs. We summarize in this review the recent development of chiral phosphoric acid (CPA)-catalyzed asymmetric dearomatization reactions.